Pollination ecology of Mesembs - Scodanibbio, Lucia (Department of Biological Sciences, 2016)
Mesembryanthemaceae is one of the main plant families in the Succulent Karoo biome of South Africa. While its pollination ecology still remains largely unstudied, the system is thought to be overall generalised. This study sought to verify whether Mesemb species flowering during September and October in Vrolijkheit Nature Reserve have generalised or specialised pollination interactions. The determinants of insect choice to a particular plant species were investigated and possible mechanisms adopted by different plant species to prevent interspecific pollen transfer were explored. The system was found to have a generalisation level of 24.7%, indicating that one of four possible interactions actually took place. A relatively high degree of overlap in insect visitors was found between the three white-flowered species (Mesemhryanthemum longistylum, Phylloholus grossus and P. splendens). Colour was one of the main determinants of insect choice, whereby Drosanthemurn speciosum, the only red-flowered species in the study showed the highest degree of specialisation. Both scent and nectar production were relatively important in attracting flower visitors. Seasonality in flowering appeared to be a very important mechanism used to reduce overlap in insect visitors, especially among intrageneric species and those that had flowers of the same colour. Daily patterns in scent and nectar production also appeared to play a role in lowering pollinator-sharing. Given the general floral structure of most Mesemb flowers, these mechanisms are likely to be very important in contributing to species reproductive isolation and the low occurrence of hybrids recorded in natural conditions.